2004
DOI: 10.1159/000075944
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Common Bile Duct Stones Leaving the Gallbladder in situ

Abstract: Background: Obstructive jaundice caused by stones is a common disorder, mostly managed by endoscopic sphincterotomy followed by cholecystectomy. The aim of this study was to evaluate whether or not clearance of the common bile duct alone is sufficient as treatment for patients with choledocholithiasis. Methods: A cohort with 447 patients with symptomatic cholecystocholedocholithiasis, undergoing endoscopic retrograde cholangiography (ERC) and if necessary sphincterotomy (ES). In 164 patients common bile duct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Because two patients in whom acute cholecystitis developed also experienced CBD stone recurrence and there was no case of cholangitis or CBD stricture, the overall recurrence rate of biliary-related events during follow-up after endoscopic CBD stone removal was 28% (28/100), which is similar to the rates of 5-24% reported www.wjgnet.com recent prospective [7] and large scale cohort studies [9] produced contrary conclusions concerning prophylactic cholecystectomy vs the wait-and-see approach. Moreover, because no consensus has been reached, the decision as to whether to operate or not is made empirically on a case-by-case basis [8,13,[17][18][19] .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Because two patients in whom acute cholecystitis developed also experienced CBD stone recurrence and there was no case of cholangitis or CBD stricture, the overall recurrence rate of biliary-related events during follow-up after endoscopic CBD stone removal was 28% (28/100), which is similar to the rates of 5-24% reported www.wjgnet.com recent prospective [7] and large scale cohort studies [9] produced contrary conclusions concerning prophylactic cholecystectomy vs the wait-and-see approach. Moreover, because no consensus has been reached, the decision as to whether to operate or not is made empirically on a case-by-case basis [8,13,[17][18][19] .…”
Section: Discussionsupporting
confidence: 77%
“…We believed that if the risk factors of acute cholecystitis in patients who receive an endoscopic CBD stone removal could be identified, we might be able to identify the indicators of prophylactic cholecystectomy, as has been mentioned by earlier investigators [13] . Some studies have compared the results of prophylactic cholecystectomy and non-surgical treatment [7,9,17] . However, as far as we know, few studies have addressed the risk factors of acute cholecystitis after endoscopic CBD stone removal in patients with GB in situ, and thus our report might be the first to focus on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in this study confirmed that endoscopic treatment alone in this group of patients was feasible treatment principle. Several other studies 1,[35][36][37] have further confirmed that octogenarians with common bile duct calculi do well with ES alone on long-term follow-up.…”
Section: Discussionmentioning
confidence: 78%
“…Aunque la principal indicación para el manejo endoscópico de la litiasis biliar sigue siendo la presencia de cálculos residuales o recidivantes, cada vez con mayor frecuencia se utiliza en pacientes con vesícula in situ, ya sea como paso preoperatorio o en casos seleccionados, como tratamiento definitivo 9,10 .…”
Section: Discussionunclassified